Chapter Wulfstan at Work: Recovering the Autographs of London, British Library, Additional 38651, fols. 57r-58v - Rudolf, Winfried (Buchreihe der Anglia / Anglia Book Series, 2019)
In this volume, scholars from different disciplines - Old English and Anglo-Latin literature and linguistics, palaeography, history, runology, numismatics and archaeology - explore what are here called 'micro-texts', i.e. very short pieces of writing constituting independent, self-contained texts. For the first time, these micro-texts are here studied in their forms and communicative functions, their pragmatics and performativity.